2011
DOI: 10.1038/ncomms1538
|View full text |Cite
|
Sign up to set email alerts
|

A guideline for atomistic design and understanding of ultrahard nanomagnets

Abstract: magnetic nanoparticles are of immense current interest because of their possible use in biomedical and technological applications. Here we demonstrate that the large magnetic anisotropy of FePt nanoparticles can be significantly modified by surface design. We employ X-ray absorption spectroscopy offering an element-specific approach to magnetocrystalline anisotropy and the orbital magnetism. Experimental results on oxide-free FePt nanoparticles embedded in Al are compared with large-scale density functional th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 46 publications
4
99
0
Order By: Relevance
“…Thus, it is not surprising that we find that bi-pyramidal structures with large central Pt layer has significantly higher MCA per atom compared to the cuboctahedral ones. 18,25 For example, we get an MCA per atom value 1.14 meV for the Fe 64 Pt 68 versus 0.86 meV reported in the papers above for the 147 atom FePt cluster reported in Ref [25]. This difference can be traced to the larger percentage of Pt atoms in the center for the bi-pyramidal case compared to the cuboctahedral structure.…”
Section: Magnetic Anisotropy Of L1 0 Fept Nanoclustersmentioning
confidence: 65%
See 4 more Smart Citations
“…Thus, it is not surprising that we find that bi-pyramidal structures with large central Pt layer has significantly higher MCA per atom compared to the cuboctahedral ones. 18,25 For example, we get an MCA per atom value 1.14 meV for the Fe 64 Pt 68 versus 0.86 meV reported in the papers above for the 147 atom FePt cluster reported in Ref [25]. This difference can be traced to the larger percentage of Pt atoms in the center for the bi-pyramidal case compared to the cuboctahedral structure.…”
Section: Magnetic Anisotropy Of L1 0 Fept Nanoclustersmentioning
confidence: 65%
“…And given the large spin-orbit coupling constant of Pt it is this enhanced orbital moment of Pt that is responsible for the higher anisotropy of the system as a whole. We also found that when the central layer of the bipyramidal cluster is Pt, the cluster has higher MCA than a cluster of the same size but with Fe as the central layer, in contrast to the cuboctahedral cases, 18,25 in which it is the surface layers that play crucial role in high MCA . This stems from the fact that when Pt atoms comprise the central layer they have more Fe atoms neighboring them, so that hybridization increases, lending them higher orbital moments than are possessed by Pt atoms in other layers.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations